Flora and Ecocenotic Arrangement of Mosses in Guzeneyevo State Complex Region-Class Reserve (Tyumen Region) (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
The flora of mosses in the Guzeneyevo reserve includes 91 species, 42 genera, 24 families, 8 orders relating to 4 classes: Sphagnopsida, Polytrichopsida, Tetraphidopsida, and Bryopsida. The Amblystegium serpens is marked by the variation of A. serpens var. juratzkanum. The mosses of the Hypnales order which amount to 39.4% of the total number of species, are the most occurring in the composition of plant associations. The next most occurring one is the Sphagnales order, with 22%, the third position is shared by Bryales and Dicranales, with 13% each. The Sphagnaceae, Polytrichaceae, Dicranaceae, and Amblystegiaceae families, the share of which is 49.4%, are characterized with the greatest variety of species. The coniferous and small-leaved forests are characterized by the greatest variety of mosses, with 65 species. The next are swamps and swamp forests, with 48 species. For the first time in the Tyumen Region we register Didimodon rigidulus and Sphagnum palustre, as well as very rare species: Atrichum undulatum, Bryum argenteum, B. moravicum, Hygroamblystegium humile, Pohlia melanodon, Sphagnum majus. The majority of mosses, 57 species, are registered on the rotting wood, 51 species are registered on the soil, and 32 species are registered on the tree-trunks. Against the degree of substrate moisture, mosses are represented by 10 ecological groups, among which mesophytes (38%), hygrophytes (10.9%), and mesohygrophytes (9.8%) dominate. Against the degree of substrate nutrition, the most remarkable from the 9 ecological groups are mesotrophs (31.5%), meso-eutrophs (17.4%), and eutrophs (12%).
Keywords: Tyumen Region, reserve, plant associations, bryoflora, mosses, systematic analysis, ecological factors.